Building and development of an organizational competence for digital transformation in SMEs - José Manuel González-Varona; Adolfo López-Paredes; David Poza; Fernando Acebes (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: The new competitive environment characterized by innovation and constant change is forcing a new organizational behavior. This requires a digital transformation of SMEs based on collective performance determinants. SMEs have particular characteristics that differentiate them from large companies and a model that allows them to identify, leverage and develop their digital capabilities can help them to advance in digital maturity. Design/methodology/approach: An in-depth review of the existing literature on digital transformation and organizational competence was carried out on Scopus and Web of Science to identify the digital challenges faced by SMEs, and what digital capabilities they have to develop to face these challenges. In order to obtain the necessary information for the refinement of organizational competence for digital transformation model, six experts were interviewed; three of them are academics and the other three are professionals with management responsibilities in SMEs. We used semi-structured interviews, to keep the interviews focused and facilitate cross-data analysis between experts. In addition, it allowed us the possibility of analyzing new relevant aspects that could arise during the interview. Findings: As a result of this study we have developed a refined model of organizational competence for digital transformation that allows SMEs to identify and develop the digital capabilities necessary to advance in the digital transformation, refined with the opinions of six experts consulted. We were able to observe the importance of organizational learning and organizational knowledge to advance the digital transformation of SMEs. Originality/value: The developed model is useful for SME managers to know what the initial starting situation is, what the digital gaps are and to be able to plan the actions to develop the necessary digital capabilities to advance towards digital maturity.
Keywords: 650; digital transformation; organizational competencies; SME; digital maturity; digital economy